2018
DOI: 10.7717/peerj.4480
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of ‘CandidatusPhytoplasma aurantifolia’ associated with witches’ broom on acid lime trees

Abstract: “Candidatus Phytoplasma aurantifolia” is associated with witches’ broom disease of lime in Oman and the UAE. A previous study showed that an infection by phytoplasma may not necessarily result in the physical appearance of witches’ broom symptoms in some locations in Oman and the UAE. This study investigated whether phytoplasma strains belonging to “Ca. P. aurantifolia” (based on the 16S rRNA gene analysis) in locations where disease symptoms are expressed are different from phytoplasma in locations where dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…A total of 174 phytoplasma-symptomatic (pathogen incidence) samples of both acid lime trees and alfalfa plants were collected at various locations in North and South Oman during a survey conducted from 2015 to 2020. The identifications and classifications of phytoplasmas of acid lime trees and alfalfa infected with phytoplasma disease were proven using molecular techniques which were conducted to amplify the 16Sr RNA gene sequence of phytoplasmas in previous studies [3,18,19]. Polymerase chain reactions (PCR) of the 16Sr RNA gene were performed by using the forward primer P1 [20] and the reverse primer P7 [21] as direct PCR.…”
Section: Species Occurrence Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 174 phytoplasma-symptomatic (pathogen incidence) samples of both acid lime trees and alfalfa plants were collected at various locations in North and South Oman during a survey conducted from 2015 to 2020. The identifications and classifications of phytoplasmas of acid lime trees and alfalfa infected with phytoplasma disease were proven using molecular techniques which were conducted to amplify the 16Sr RNA gene sequence of phytoplasmas in previous studies [3,18,19]. Polymerase chain reactions (PCR) of the 16Sr RNA gene were performed by using the forward primer P1 [20] and the reverse primer P7 [21] as direct PCR.…”
Section: Species Occurrence Datamentioning
confidence: 99%
“…The R16F2n/R16R2 primer pair was used for the nested PCR. The 16Sr DNA sequences results of infected acid lime trees and alfalfa plants samples showed that the phytoplasmas belong to 16SrII-B and 16SrII-D subgroups [1,3,18,19]. The data were gathered from various farms of acid lime trees infected with 16SrII-B phytoplasma (87 locations) and alfalfa infected with 16SrII-D phytoplasma (87 locations) (see Figure 1).…”
Section: Species Occurrence Datamentioning
confidence: 99%
“…This silent infection was observed through molecular testing of plant material, yet the host plants themselves show no obvious visible symptoms. These infected trees do however, also collapse within the 5 year post infection period [13], making this asymptomatic variant potentially even more of a threat to global lime production.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for a finer characterization of 'Ca. P. aurantifolia' strains, several regions of the phytoplasma genome are investigated (Siampour et al 2013;Al-Abadi et al 2016;Al-Ghaithi et al 2018). Imp is one of the three main types of immunodominant membrane proteins (IDP) identified in phytoplasmas.…”
Section: Introductionmentioning
confidence: 99%
“…Variability analyses of imp genes allowed the identification of three phylogenetic subgroups (A, B, and C) among 'Ca. P. aurantifolia' related strains (16SrII), with WBDL phytoplasma clustering within subgroup C. However, WBDL phytoplasma strains from Mexican lime trees throughout Oman, UAE, and Iran (Al-Abadi et al 2016), as well as different geographical (semitropical, subtropical, and desert) regions (Al-Ghaithi et al 2018), Shared 99.8 to 100% imp gene sequence similarity to each other.…”
Section: Introductionmentioning
confidence: 99%